The information efficiency of the South African corporate bond market in relation to earnings announcements - Ravele, Mpho Krezentia (My University, 2016)
Corporate bonds issued by the four major commercial banks in South Africa, which account for 61% of the market, and their respective earning announcements in the period 1 January 2013 to 31 December 2014 were used to analyse the reaction of daily corporate bond prices to the earnings announcements of South African companies. The reaction of the daily corporate bond prices to earnings announcements was empirically analysed using cross sectional regressions. We concluded that on average the South African corporate bond market incorporates any new information from earnings announcements. We also investigated if the asymmetrical payoff structure of corporate bonds causes daily prices to be more sensitive to bad earnings announcements than good earnings announcements. Our investigation found that daily corporate bond prices are insensitive to both bad and good earnings announcements. Lastly, we analysed if the lack of infrastructure and liquidity in the corporate bond market hinders corporate bonds in incorporating information relative to the stock market, which has better infrastructure and liquidity. We observed that both corporate bonds and stocks on average incorporate new information from earnings announcements, irrespective of illiquidity and the absence of adequate infrastructure in the South African corporate bond market,
Thesis (M.M. (Finance & Investment)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits Business School, 2016
Keywords: Capital market--South Africa.; Corporations--South Africa--Finance; Bond market--South Africa